2015
DOI: 10.1208/s12249-015-0438-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Status on the Gastrointestinal Transit of Amphotericin B-Containing Solid Lipid Nanoparticles in Rats

Abstract: Abstract. Amphotericin B (AmB) is poorly absorbed from the gastrointestinal tract. Recent studies have suggested enhanced drug absorption from solid lipid nanoparticles (SLN). Little is known of the fate of AmB absorption within the gastrointestinal tract, and no gastrointestinal transit study has yet been performed on AmB-containing nano-formulations. We aimed to investigate the effect of food on the gastrointestinal transit properties of an AmB-containing SLN in rats. Three SLNs containing AmB, paracetamol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The obtained data revealed that rate absorption of AmB from SLNs decreased with the presence of food, contrary to the extent of absorption that remained practically unchanged [240]. Regardless of the food status, these results suggested that amphotericin SLNs could be mainly taken up by the lymph, with the small intestine as the best delivery site for the prepared nanoformulation [240].…”
Section: Solid Lipid Nanoparticles and Nanostructured Lipid Carriersmentioning
confidence: 92%
See 4 more Smart Citations
“…The obtained data revealed that rate absorption of AmB from SLNs decreased with the presence of food, contrary to the extent of absorption that remained practically unchanged [240]. Regardless of the food status, these results suggested that amphotericin SLNs could be mainly taken up by the lymph, with the small intestine as the best delivery site for the prepared nanoformulation [240].…”
Section: Solid Lipid Nanoparticles and Nanostructured Lipid Carriersmentioning
confidence: 92%
“…The improved bioavailability observed with oral delivery of SLNs could be related to an increase of residence time within the gut due to the interactions of lipids on the surface of NPs with the epithelial membranes [160]. Gastric and intestinal enzymes are prone to degrade lipid-based delivery systems and absorption can be enhanced in the course of the digestion of triglycerides from SLNs by pancreatic lipase [239,240]. Stability, drug release behavior, and in vivo performance of SLNs are also related to the location of the drug in the lipid matrix.…”
Section: Solid Lipid Nanoparticles and Nanostructured Lipid Carriersmentioning
confidence: 99%
See 3 more Smart Citations